Morphology and Morphometry of the Olfactory Rosette of a Teleostean Fish: Catla catla (Ham.) - Kumari, K. (Our Nature, 2009)
The morphological structure and morphology of the olfactory organs in a freshwater, aquatic breathing fish, Catla catla (Ham.) has been described. It consists of two nasal openings on each side of the head, the anterior and posterior nasal opening with a prominent nasal flap in between. A pair of olfactory rosettes is lodged in the depression called olfactory pits or olfactory chambers. The olfactory rosettes are oval, cup shaped structures. Each rosette bears a series of olfactory lamellae on each side of the median raphe. A single lamella is a flat, bifid tongue like structure. Measurements of the dimension of olfactory rosettes have been made and the data were analysed with respect to body weight using logarithmic transformations, Y = awb. The total number of lamellae in the olfactory rosette increased with increase in body weight. With unit increase in body weight, the total number of lamellae increased by a power (b) of 0.2603, while the total surface area of lamellae increased by power of (b) 0.636. Both the parameters showed highly significant correlation coefficient i.e. r = 0.9894; P < 0.001 and r = 0.95218; P < 0.001 respectively. Key words: Catla catla, Olfactory organ, Morphology, Morphometrics doi: 10.3126/on.v6i1.1652 Our Nature (2008)6:30-37